ANALISIS RISIKO DENGAN PENDEKATAN METODE RISK MATRIX PADA PENYELESAIAN PEKERJAAN KONSTRUKSI INCOMER SUTT 150 kV GI TEMPADUNG – GI KTT PT MITRA MURNI PERKASA (MMP) - Punang Jati Arso; Reysha Rizki Amanda Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Incomer construction project for the 150 kV High Voltage Overhead Line (SUTT) connecting GI Tempadung and GI KTT PT Mitra Murni Perkasa (MMP) in Balikpapan, East Kalimantan, faces various construction risks due to challenging physical site conditions and its proximity to an active existing transmission network. This study aims to identify potential risks, measure risk levels, and formulate mitigation strategies using the Risk Matrix method based on the ISO 31000:2018 risk management framework. The study applies a quantitative approach through a case study method. Primary data were collected through questionnaires and interviews with 30 respondents from PLN UIP, PLN UPP, PLN Pusmanpro/MK, and the executing contractor, selected using purposive sampling. Risk levels were calculated using the equation R = P x I, then mapped into three categories: low, medium, and high. The study identified 54 risk indicators across 10 variable groups. The research instrument proved valid in substance and highly reliable, with a Spearman-Brown coefficient of 0.980. The Risk Matrix analysis produced 2 High Risk variables, 30 Medium Risk variables, and 22 Low Risk variables. The highest risks stem from extreme weather (R = 17.12) and difficult access to tower foundation sites (R = 15.08). The recommended mitigation strategy combines Risk Acceptance and Risk Mitigation, including real-time weather monitoring, adaptive work scheduling, and planning of dedicated access routes to tower points.